A multifunctional synergistically modified silicon-magnesium-aluminum powder, a preparation method and application thereof

CN122878631APending Publication Date: 2026-10-09JILIN DADINGSHAN HUANCHUAN NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611064731.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-17
Publication Date
2026-10-09

AI Technical Summary

Benefits of technology

本发明的多官能团协同改性硅镁铝粉,通过设计小分子锚点层结合大分子功能层的双层结构,实现了大分子多官能团助剂在粉体表面的高密度、均匀接枝,有效克服了传统直接接枝法中空间位阻导致的接枝率低、分布不均的缺陷;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to inorganic powder surface modification technology and polyolefin composite material technical field, especially relates to a kind of multi-functional group synergistic modification silicon-magnesium-aluminum powder and its preparation method and application, including: natural layered silicon-magnesium-aluminum powder base, and multi-functional group interface modification layer grafted on the surface of the silicon-magnesium-aluminum powder by chemical bonding mode;The multi-functional group interface modification layer is formed by the amino anchor point layer of small molecule aminosilane coupling agent, and the macromolecular mixed additive grafted on the amino anchor point layer by amide bond jointly constitute;The multi-functional group synergistic modification silicon-magnesium-aluminum powder of the application, by designing the double-layer structure of small molecule anchor point layer combined macromolecular functional layer, realizes the high density, uniform grafting of macromolecular multi-functional group additive on the surface of powder, effectively overcome the defects of low grafting rate and uneven distribution caused by steric hindrance in traditional direct grafting method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of inorganic powder surface modification technology, and in particular to a multifunctional group synergistic modified silicon-magnesium-aluminum powder, its preparation method and application. Background Technology

[0002] Polypropylene, as a general-purpose plastic with excellent comprehensive performance and controllable cost, is increasingly widely used in automotive interior and exterior trim, home appliance housings, pipes and sheets, and other fields. With the continuous improvement of the requirements for lightweight and high performance in automobiles, its core components have put forward higher requirements for the rigidity, strength and impact toughness of PP materials. Modification by filling with inorganic mineral powder is the mainstream technical approach to improve the mechanical properties of PP, and the surface characteristics and interfacial compatibility of the powder directly determine the upper limit of the performance of the composite material.

[0003] For example, traditional mineral fillers such as talc, mica, kaolin, and calcium carbonate are commonly used in the industry to modify polyolefins. However, these fillers generally suffer from problems such as limited functionality, poor interfacial compatibility, limited reinforcement effect, and difficulty in balancing rigidity and toughness. While conventional fillers can improve the flexural modulus and rigidity of PP, they often cause a significant decrease in impact toughness, making it difficult to meet the requirements of automotive parts for a balance of rigidity and toughness, impact resistance, and high durability. In addition, traditional mineral fillers have strong surface polarity and a high tendency to agglomerate, which can easily form defect points in the resin matrix, resulting in low stress transfer efficiency, large fluctuations in the mechanical properties of the products, and some high-hardness fillers can also aggravate the wear of processing equipment and increase production costs.

[0004] In recent years, with the development of new mineral resources, a type of silica-magnesium-aluminum powder derived from newly discovered mines has gradually become a core functional filler for modifying high-performance plastics. This silica-magnesium-aluminum powder is a carefully selected natural layered silicate mineral with a unique nano- to micron-scale lamellar structure, suitable Mohs hardness, and stable silicon-magnesium-aluminum coordination structure. Compared with traditional lamellar fillers, it can maintain or even slightly optimize the impact toughness of PP while improving its rigidity and strength, showing excellent potential for a balance between rigidity and toughness. However, the surface of this silica-magnesium-aluminum powder is rich in hydroxyl groups and has strong hydrophilicity, resulting in extremely poor compatibility with the non-polar PP matrix interface. Direct use will lead to powder agglomeration, weak interfacial bonding, and low stress transfer efficiency, failing to leverage the reinforcing, toughening, and barrier advantages brought by its lamellar structure.

[0005] To improve the interfacial compatibility between inorganic powders and polyolefin matrices, traditional techniques typically employ silane coupling agents to treat the inorganic powders. For example, the alkoxysilane (-Si(OR)3) at one end of the silane coupling agent reacts with the hydroxyl groups on the powder surface, while the other end carries an organic functional group such as amino or vinyl groups that can interact with organic resins, thus creating a "molecular bridge" between the inorganic powder and the organic resin. However, silane coupling agents have limited functionality. When using multifunctional macromolecular additives with more complex structures and comprehensive functions, such as silanes with long-chain alkyl and epoxy / anhydride groups, theoretically multiple functions such as anchoring, compatibility, and reactive bonding can be achieved simultaneously. However, in actual grafting processes, due to their large molecular size, especially the extended long-chain alkyl groups, a significant spatial shielding effect occurs. When an additive molecule is successfully grafted onto the powder surface, its extended molecular chain acts like an open umbrella, physically preventing other additive molecules from approaching and contacting the powder surface, making subsequent grafting reactions difficult.

[0006] This steric hindrance effect directly results in extremely low density and uneven distribution of additives on the powder surface. Only a small amount of additives are grafted at some isolated points, while most of the surface area remains exposed and unmodified in a hydrophilic state. Consequently, the modified layer on the surface of the modified silicon-magnesium-aluminum powder is incomplete and discontinuous. When melt-blended with PP, the exposed areas will still agglomerate. The small amount of grafted additives cannot provide enough reactive groups to form a strong chemical bond with the PP matrix. This results in the tensile strength and flexural modulus of the composite material being far lower than expected, and the impact performance may even deteriorate. The novel silicon-magnesium-aluminum powder cannot achieve the rigidity-toughness balance advantage it should possess.

[0007] Therefore, there is an urgent need to provide a multifunctional synergistic modified silicon-magnesium-aluminum powder and its preparation method, so as to achieve uniform and high-density anchoring of additive molecules on the powder surface, thereby giving full play to its multifunctional synergistic modification effect. Summary of the Invention

[0008] The purpose of this invention is to provide a multifunctional group synergistic modified silicon-magnesium-aluminum powder, its preparation method and application. By adopting a stepwise strategy of small molecule pre-anchoring and macromolecule post-grafting, the invention solves the problem of low grafting density and uneven distribution caused by steric hindrance when multifunctional group macromolecular mixed additives are grafted onto the surface of silicon-magnesium-aluminum powder.

[0009] To achieve the above objectives, the present invention adopts the following technical solution: The present invention provides a multifunctional group synergistic modified silicon-magnesium-aluminum powder, comprising: a natural layered silicon-magnesium-aluminum powder substrate, and a multifunctional group interface modification layer grafted onto the surface of the silicon-magnesium-aluminum powder by chemical bonding. The multifunctional interface modification layer is composed of an amino anchor layer formed by a small molecule aminosilane coupling agent and a macromolecular mixed agent grafted onto the amino anchor layer via amide bonds. The natural layered silica-magnesium-aluminum powder is composed of the following components by mass percentage (100%): ≥28.0% SiO2, ≥32.0% MgO, ≥15.0% Al2O3, ≤3.0% CaO, ≤3.0% Fe2O3, and 10.0-20.0% loss on ignition. The natural layered magnesium-silicon aluminum powder has a particle size D50 of 3-10 μm and a specific surface area of ​​8-15 m². 2 / g, Mohs hardness is 2.6-3.3.

[0010] Furthermore, the small molecule aminosilane coupling agent is γ-aminopropyltriethoxysilane or γ-aminopropyltrimethoxysilane.

[0011] Furthermore, the macromolecular mixing agent is a long-chain alkyl-maleic anhydride monoester-silane.

[0012] Furthermore, the long-chain alkyl group in the long-chain alkyl-maleic anhydride monoester-silane has 10-18 carbon atoms, and its general structural formula is CnH. 2n+1 -O-CO-CH=CH-CO-NH-(CH2)3-Si(OC2H5)3.

[0013] This invention provides a method for preparing multifunctional group synergistically modified silicon-magnesium-aluminum powder, comprising the following steps: S1. Place the dry natural layered magnesium-silicon aluminum powder in a high-speed mixer, mix and dilute the small molecule aminosilane coupling agent with anhydrous ethanol at a volume ratio of 1: (2-4), atomize and spray it in, heat it at 100-120℃ for 10-20 min, and then form an amino anchor layer on the surface of the powder to obtain pre-anchored powder. S2. Determine the amount of amino grafting on the surface of the pre-anchored powder obtained in step S1 using acid-base titration or elemental analysis. Calculate the required amount of macromolecular mixing agent based on the measured amount of amino grafting per gram of powder, so that the molar ratio of amino to macromolecular mixing agent is 1:(0.8-1.2). S3. Disperse the pre-anchored powder obtained in step S1 in an anhydrous organic solvent. The mass-volume ratio of the powder to the anhydrous organic solvent is 1g:3-8ml. Disperse the powder by ultrasonication to form a stable suspension. S4. Dissolve the macromolecular mixed additive calculated in step S2 in an anhydrous organic solvent accounting for 1 / 10-1 / 5 of the total volume to obtain an additive solution. Under nitrogen protection, slowly add the additive solution dropwise to the stable suspension in step S3. The dropwise addition time is controlled at 30-60 min. After the dropwise addition is completed, heat to 40-60℃ and stir for 2-6 h. During the reaction, take a sample every hour for Fourier transform infrared spectroscopy monitoring. When the characteristic absorption peak of the anhydride group near the wavenumber of 1780-1850 disappears, the reaction is judged to have reached the endpoint. The carboxyl group at the end of the macromolecular mixed additive undergoes an amidation reaction with the amino group on the surface of the powder, and the macromolecular mixed additive is grafted onto the amino anchor layer to obtain the reaction product. S5. Filter the reaction product from step S4 and wash it 2-3 times with the same anhydrous organic solvent as in step S3. Each time, the mass-to-volume ratio of the filter cake to the solvent is 1g:2-5ml. Stir and wash for 10-15min and then vacuum dry at 60-80℃ for 4-8h to obtain multifunctional synergistic modified silicon-magnesium-aluminum powder. The activation index of the multifunctional synergistic modified silicon-magnesium-aluminum powder is ≥95% and the contact angle is >105°.

[0014] Further, in step S1, the amount of the small molecule aminosilane coupling agent is 0.5-2.0% of the mass of the natural layered magnesium-silica powder.

[0015] Further, in step S3, the anhydrous organic solvent is anhydrous tetrahydrofuran, anhydrous dichloromethane, or anhydrous toluene.

[0016] Furthermore, in step S5, the vacuum degree of the vacuum drying is ≤-0.08MPa.

[0017] Another aspect of the present invention provides the application of multifunctional group synergistic modified silica-magnesium-aluminum powder in polypropylene composite materials, wherein the polypropylene composite material is composed of the following components by mass parts: 100 parts polypropylene resin, 10-50 parts multifunctional group synergistic modified silica-magnesium-aluminum powder, 0.1-0.5 parts antioxidant, and 0.1-0.5 parts lubricant. Wherein, the polypropylene resin is homopolymer polypropylene or copolymer polypropylene; The antioxidant is one or more of antioxidant 1010, antioxidant 1076, and antioxidant 168; The lubricant is calcium stearate, zinc stearate, or polyethylene wax; The polypropylene composite material is used to manufacture automotive bumpers, dashboards, or door panel structural components.

[0018] Furthermore, the preparation method of the polypropylene composite material includes the following steps: Polypropylene resin, multifunctional synergistic modified magnesium-aluminum silicate powder, antioxidant, and lubricant are added to a high-speed mixer and mixed at 500-800 rpm for 3-5 minutes. Then, the mixture is fed into a twin-screw extruder for multi-segment melt blending. The extruder temperatures are set as follows: Zone 1 160-180℃, Zone 2 180-200℃, Zones 3 / 4 190-210℃, Zone 5 180-200℃, and the die head temperature 180-200℃. The screw speed is 250-350 rpm, and the feed speed is 15-25 rpm. The material is extruded, cooled, and granulated to obtain polypropylene composite material particles; Polypropylene composite material particles are injection molded on an injection molding machine at an injection temperature of 190-210℃ and a mold temperature of 30-50℃.

[0019] Compared with the prior art, the present invention has the following beneficial effects: The multifunctional group synergistic modified silicon-magnesium-aluminum powder of the present invention achieves high-density and uniform grafting of macromolecular multifunctional group additives on the powder surface by designing a double-layer structure combining a small molecule anchor layer and a macromolecular functional layer, effectively overcoming the defects of low grafting rate and uneven distribution caused by steric hindrance in the traditional direct grafting method. The present invention provides a method for preparing multifunctional group synergistic modified silicon-magnesium-aluminum powder. First, small molecule aminosilane is uniformly and densely anchored on the powder surface. Then, it is used as a reaction site to carry out an efficient amidation reaction with macromolecular mixing aids. The method decomposes the one-step macromolecular grafting problem into the steps of small molecule anchoring and macromolecular reaction. The process conditions are mild and highly controllable, making it suitable for industrial scale-up production. The multifunctional synergistic modification of magnesium-silicon aluminum powder of the present invention is applied to polypropylene composite materials. Due to the stepwise modification strategy of "small molecule pre-anchoring - macromolecule grafting", the macromolecular additives are grafted onto the surface of magnesium-silicon aluminum powder with high density and uniformity through amide bonds, forming a complete and dense multifunctional interface layer. On the one hand, the C in the macromolecular additives 18The long-chain alkyl groups, through van der Waals forces and segment entanglement, significantly improve the compatibility and dispersibility of the powder with the PP matrix, ensuring uniform powder distribution within the resin and preventing agglomeration and interfacial defects. Furthermore, the carbon-carbon double bonds retained in the macromolecular additive molecules can undergo free radical grafting reactions with macromolecular free radicals generated on the PP molecular chains under the influence of heat and shear forces during high-temperature melt blending, forming stable chemical bonds. Simultaneously, on the pre-anchored layer on the powder surface, unreacted trace amounts of free carboxyl groups interact with the polar end groups of the PP molecular chains or the polar end groups of additives such as antioxidants. The functional groups can form hydrogen bonds or dipole-dipole interactions to achieve multiple interfacial anchoring. In addition, the amide and ester bonds grafted onto the powder surface provide a certain degree of polarity and flexibility to the interfacial layer, which helps to effectively transfer and disperse stress at the interface. Through the synergistic effect of these chemical bonds and physical entanglements, the tensile strength, flexural strength and flexural modulus of PP composite materials can be significantly improved, while the impact performance is slightly improved. This achieves an excellent balance of rigidity and toughness, and also has the characteristics of good processing fluidity and improved heat resistance. It is particularly suitable for high-performance structural parts such as automotive bumpers, dashboards and door panels. Attached Figure Description

[0020] Figure 1 This is a scanning electron microscope (SME) image of the natural layered magnesium silicate aluminum powder of this invention.

[0021] Figure 2 This is a graph showing the TG & DTG step analysis and data results of the natural layered magnesium silicate aluminum powder of this invention. Detailed Implementation

[0022] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. However, those skilled in the art will understand that the embodiments described below are some embodiments of the present invention, but not all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0023] Unless otherwise specified, the post-processing operations described below, such as "mixing", "vacuum", "heating", "ultrasonic dispersion", "stirring", "vacuum filtration", "reduced pressure distillation", "melt blending", "injection molding", and "extrusion", can be selected by those skilled in the art based on actual conditions, and are not further limited.

[0024] The raw materials and preparation tools used in the following preparation examples, embodiments, and comparative examples are all commercially available industrial products, including: natural layered magnesium-aluminum silicate powder, which is derived from newly discovered mines and has a unique nano- to micron-layered structure with a Mohs hardness of 2.6-3.3. (See Appendix) Figure 1-2 The SEM and TG & DTG detection images and text data are shown. The loss on ignition of the components is obtained by firing in a muffle furnace at 1000℃ for 1 hour. The specification for γ-aminopropyltriethoxysilane is (KH550), and its molecular formula is C9H. 23 NO3Si, purity ≥98%, purchased from Nanjing Shuguang Chemical Group Co., Ltd. Anhydrous ethanol was of analytical grade with a purity of ≥99.7% and was purchased from Xuzhou Wanbo Biotechnology Co., Ltd. Anhydrous tetrahydrofuran was purchased from Shanghai Mairui Biochemical Technology Co., Ltd. with analytical grade and moisture content ≤0.005%. Anhydrous dichloromethane was purchased from Shandong Weijin Chemical Technology Co., Ltd. with analytical grade and moisture content ≤0.005%. Anhydrous toluene was of analytical grade with a moisture content of ≤0.005%, and was purchased from Jiangsu Jiebeiming Chemical Materials Co., Ltd. Homopolymer polypropylene or copolymer polypropylene was purchased from Shanghai Bohr Chemical Reagent Co., Ltd. Antioxidant 1010, Antioxidant 1076, and Antioxidant 168 are all industrial grade and were purchased from BASF, Germany; calcium stearate, zinc stearate, or polyethylene wax were purchased from Shandong Gaomi Youhe Additives Co., Ltd. The specifications of octadecyl alcohol are analytical grade, purity ≥99%, melting point 56-58℃, and it was purchased from Shanghai Mairui Biochemical Technology Co., Ltd. Lauryl alcohol (dodecyl alcohol) was purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd. with the following specifications: analytical grade, purity ≥99%, melting point 22-26℃. Maleic anhydride was purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd. with specifications of analytical grade, purity ≥99%, and melting point 51-54℃. p-Toluenesulfonic acid was purchased from Shanghai Maclean Biochemical Technology Co., Ltd. with an analytical grade and a purity of ≥98.5%. The specifications of dicyclohexylcarbodiimide were analytical grade, purity ≥99%, and it was purchased from Asiatalent Chemical Limited. 4-Dimethylaminopyridine was purchased from Shanghai Anpu Experimental Technology Co., Ltd. with analytical grade and purity ≥99%.

[0025] Preparation Example 1 Macromolecular mixed additives (eighteen-carbon chain product long-chain alkyl-maleic anhydride monoester-silane (C 28 H 55 NO6Si) and long-chain alkyl maleic acid monoester (C 22 H 40 The preparation steps of O4 are as follows: A1. Dissolve 135g (0.5mol) of octadecyl alcohol in 500ml of anhydrous toluene, add 51g (0.525mol, molar ratio 1:1.05) of maleic anhydride and 0.5g of p-toluenesulfonic acid as a catalyst, and reflux at 110-120℃ for 4h. Continuously remove the water generated in the reaction through a water separator. After the reaction is completed, remove toluene and unreacted maleic anhydride by vacuum distillation to obtain a white waxy solid long-chain alkyl maleic acid monoester intermediate. A2. Dissolve 180g of the above-mentioned long-chain alkyl maleic acid monoester (approximately 0.4mol) in 800ml of anhydrous dichloromethane. Under nitrogen protection, slowly add 44.3g (0.2mol) of γ-aminopropyltriethoxysilane (KH550), along with 41.3g (0.2mol) of dicyclohexylcarbodiimide as a condensing agent and 1.2g (0.01mol) of 4-dimethylaminopyridine as a catalyst. Stir the reaction at room temperature for 12h. After the reaction is complete, filter to remove the insoluble matter of dicyclohexylurea. Wash the filtrate successively with 5% sodium bicarbonate solution and saturated brine, dry with anhydrous sodium sulfate, and remove the solvent by vacuum distillation to obtain a pale yellow waxy solid macromolecular mixed auxiliary containing the 18-carbon chain product long-chain alkyl-maleic anhydride monoester-silane and the long-chain alkyl maleic acid monoester intermediate.

[0026] Preparation Example 2 Macromolecular Mixture Additives (Twelve-C Chain Product Long-Chain Alkyl-Maleic Anhydride Monoester-Silane (C 22 H 43 NO6Si) and long-chain alkyl maleic acid monoester (C 16 H 28 The preparation steps of O4) are the same as those in Preparation Example 1, except that the raw materials are different and the products are different. Specifically, 135g (0.5mol) of octadecyl alcohol is replaced with 93g (0.5mol) of lauryl alcohol, and the amount of feed is adjusted accordingly to obtain a light yellow paste-like twelve-carbon chain product, long-chain alkyl-maleic anhydride monoester-silane and long-chain alkyl maleic acid monoester.

[0027] Example 1 A method for preparing multifunctional synergistically modified silicon-magnesium-aluminum powder includes the following steps: S1. Take 1000g of natural layered magnesium-silica aluminum powder dried at 100℃ for 4h and place it in a 20L high-speed mixer and stir at 600rpm. Mix and dilute 10g of γ-aminopropyltriethoxysilane with 30ml of anhydrous ethanol and atomize it into the powder. Heat it at 110℃ for 15min while increasing the stirring speed to 1000rpm to form an amino anchor layer on the powder surface to obtain pre-anchored powder. S2. The amount of amino grafting on the surface of the pre-anchored powder obtained in step S1 was determined by acid-base titration. Specifically, 2.0 g of the pre-anchored powder was added to 50 ml of a 0.1% hydrochloric acid standard solution and ultrasonically dispersed for 30 min to allow the amino groups to fully react with the acid. The powder was removed by filtration, and 20 ml of the filtrate was back-titrated with a 0.1% sodium hydroxide standard solution. Phenolphthalein was used as an indicator, and the amount of amino (-NH2) grafting on the surface of the pre-anchored powder was calculated to be 0.28 mmol / g. Based on the determined amount of amino grafting, the required amount of macromolecular mixed additive was calculated so that the molar ratio of amino groups on the surface of the pre-anchored powder to free carboxyl groups in the macromolecular mixed additive was 1:1.0. Therefore, 560 mmol of macromolecular mixed additive was required, and 263 g of the macromolecular mixed additive obtained in Preparation Example 1 was used. S3. In a 10-liter reactor, 1 kg of the pre-anchored powder obtained in step S1 is dispersed in 6 L of anhydrous tetrahydrofuran and ultrasonically dispersed at 300 rpm for 30 min to form a stable suspension. S4. Dissolve 263g of the macromolecular mixed auxiliaries calculated in step S2 in 600ml of anhydrous tetrahydrofuran to obtain an auxiliary solution. Under nitrogen protection, slowly add the auxiliary solution dropwise to the stable suspension in step S3 over 40min through a constant pressure dropping funnel. After the addition is completed, heat to 50℃ and stir for 4h to react. The macromolecular mixed auxiliaries are grafted onto the amino anchor layer through amide bonds to obtain the reaction product. It should be noted that, to verify the completeness of the reaction in step S4, after the addition was completed, the temperature was raised to 50°C and the reaction was stirred for 4 hours. Samples were then taken for Fourier transform infrared spectroscopy (FTIR) monitoring. The free carboxyl groups were observed at 1710 cm⁻¹. -1 The absorption peak near the 1650 cm⁻¹ drops to below 5% of the initial intensity, indicating that the free carboxyl group has essentially participated in the amidation reaction, while the amide bond at 1650 cm⁻¹... -1 Nearby and at 1560cm -1 The enhanced and stable absorption peaks in the vicinity indicate that the amidation reaction has reached equilibrium. This signifies that the reaction has reached its endpoint, meaning that the free carboxyl groups carried by the unreacted monoesters in the macromolecular mixed additive have fully undergone amidation with the amino groups on the surface of the pre-anchored powder.

[0028] S5. The reaction product in step S4 is subjected to vacuum filtration. A Buchner funnel and a filtration flask are used to collect the filter cake. The filter cake is washed three times with anhydrous tetrahydrofuran, with 3L of anhydrous tetrahydrofuran added each time. After stirring and washing for 10 minutes, the filter cake is filtered. The washed filter cake is transferred to a vacuum drying oven and vacuum dried at 70℃ and a vacuum degree of -0.08MPa for 6 hours to obtain multifunctional group synergistic modified silicon magnesium aluminum powder. The activation index of the multifunctional group synergistic modified silicon magnesium aluminum powder is ≥95%, and the contact angle is >105°.

[0029] The application of a multifunctional group synergistic modified silica-magnesium-aluminum powder in polypropylene composites, wherein the polypropylene composites, by mass parts, comprise: 100 parts homopolymer polypropylene, 40 parts multifunctional group synergistic modified silica-magnesium-aluminum powder, 0.2 parts antioxidant 1010 and 0.1 parts antioxidant 168, and 0.3 parts zinc stearate. The preparation method of the polypropylene composite material includes the following steps: Polypropylene resin, multifunctional synergistic modified magnesium aluminum silicate powder, antioxidant, and lubricant were added to a 10L high-speed mixer and mixed at 600rpm for 3 minutes. The uniformly mixed material is fed into a twin-screw extruder for multi-segment melt blending. The temperatures of each segment of the extruder are set as follows: 170℃ for the first segment, 190℃ for the second segment, 200℃ for the third segment, 205℃ for the fourth segment, 200℃ for the fifth segment, and 190℃ for the die head. The screw speed is 300 rpm and the feed speed is 20 rpm. The material is extruded, cooled, and granulated to obtain polypropylene composite material particles; Polypropylene composite particles were injection molded into standard test specimens on an injection molding machine. The injection temperature was 200℃, the mold temperature was 40℃, the injection pressure was 80MPa, the holding pressure was 40MPa, the holding time was 5s, and the cooling time was 20s.

[0030] Example 2 A method for preparing multifunctional synergistically modified silicon-magnesium-aluminum powder differs from that in Example 1 in that... In step S1, the amount of γ-aminopropyltriethoxysilane was adjusted to 20g, and the heating conditions were 120℃ for 10min. In step S2, the amount of amino (-NH2) grafted onto the surface of the pre-anchored powder was calculated to be 0.41 mmol / g, and the total amino content was 410 mmol. Based on the measured amount of amino grafting, the required amount of macromolecular mixed additive was calculated so that the molar ratio of amino to free carboxyl groups in the macromolecular mixed additive was 1:0.8. Therefore, 656 mmol of macromolecular mixed additive was required, and 308.5 g of the macromolecular mixed additive obtained in Preparation Example 1 was used. In step S4, 308.5g of the macromolecular mixed additive calculated in step S2 is used.

[0031] The application of a multifunctional group synergistic modified silica-magnesium-aluminum powder in a polypropylene composite material, wherein the polypropylene composite material differs from that in Example 1 in that the multifunctional group synergistic modified silica-magnesium-aluminum powder is 25 parts, antioxidant 1010 and antioxidant 168 are 0.1 parts, and zinc stearate is 0.3 parts. The preparation method of the polypropylene composite material is the same as that in Example 1.

[0032] Example 3 A method for preparing multifunctional synergistically modified silicon-magnesium-aluminum powder differs from that in Example 1 in that... In step S1, the amount of γ-aminopropyltriethoxysilane was adjusted to 5g, and the heating conditions were 100℃ for 20min. In step S2, the amount of amino (-NH2) grafted onto the surface of the pre-anchored powder was calculated to be 0.18 mmol / g, and the total amino content was 180 mmol. Based on the measured amount of amino grafting, the required amount of macromolecular mixed additive was calculated so that the molar ratio of amino to free carboxyl groups in the macromolecular mixed additive was 1:1.2. Therefore, 432 mmol of macromolecular mixed additive was required, and 203.1 g of the macromolecular mixed additive obtained in Preparation Example 1 was used. In step S4, 203.1g of the macromolecular mixed additive calculated in step S2 is used.

[0033] The application of a multifunctional group synergistic modified silica-magnesium-aluminum powder in a polypropylene composite material, wherein the polypropylene composite material differs from that in Example 1 in that the multifunctional group synergistic modified silica-magnesium-aluminum powder is 48 parts, antioxidant 1010 and antioxidant 168 are 0.1 parts, and zinc stearate is 0.3 parts. The preparation method of the polypropylene composite material is the same as that in Example 1.

[0034] Example 4 A method for preparing multifunctional synergistically modified silicon-magnesium-aluminum powder differs from that in Example 1 in that... In step S2, 232g of the macromolecular mixed auxiliaries obtained in Preparation Example 2 are used; In step S4, 232g of the macromolecular mixed additive calculated in step S2 is used.

[0035] The application of a multifunctional group synergistic modified silica-magnesium-aluminum powder in polypropylene composites is the same as in Example 1; The preparation method of the polypropylene composite material is the same as that in Example 1.

[0036] Example 5 A method for preparing multifunctional group synergistically modified silicon-magnesium-aluminum powder, the specific implementation method is the same as in Example 1.

[0037] The application of a multifunctional group synergistic modified silica-magnesium-aluminum powder in polypropylene composites, wherein the polypropylene composites differ from those in Example 1 in that equal parts by mass of copolymer polypropylene are used instead of homopolymer polypropylene. The preparation method of the polypropylene composite material is the same as that in Example 1.

[0038] Example 6 A method for preparing multifunctional group synergistically modified silicon-magnesium-aluminum powder, the specific implementation method is the same as in Example 1.

[0039] The application of a multifunctional group synergistic modified silica-magnesium-aluminum powder in polypropylene composite material differs from that in Example 1 in that the polypropylene composite material, by mass parts, comprises: 100 parts homopolymer polypropylene, 10 parts multifunctional group synergistic modified silica-magnesium-aluminum powder, 0.075 parts antioxidant 1010 and 0.025 parts antioxidant 168, and 0.1 parts zinc stearate. The preparation method of the polypropylene composite material is the same as that in Example 1.

[0040] Example 7 A method for preparing multifunctional group synergistically modified silicon-magnesium-aluminum powder, the specific implementation method is the same as in Example 1.

[0041] The application of a multifunctional group synergistic modified silica-magnesium-aluminum powder in polypropylene composite material differs from that in Example 1 in that the polypropylene composite material, by mass parts, comprises: 100 parts homopolymer polypropylene, 50 parts multifunctional group synergistic modified silica-magnesium-aluminum powder, 0.3 parts antioxidant 1010 and 0.2 parts antioxidant 168, and 0.5 parts zinc stearate. The preparation method of the polypropylene composite material is the same as that in Example 1.

[0042] Comparative Example 1 A one-step method for preparing modified magnesium-aluminum silicate powder: 1 kg of natural layered magnesium-aluminum silicate powder, which was dried at 100°C for 4 h in the same batch as in Example 1, was placed in a 20L high-speed mixer. 171g of the octadecane chain product long-chain alkyl-maleic anhydride monoester-silane auxiliary agent prepared in Preparation Example 1 was dissolved in 500ml of anhydrous ethanol to obtain the auxiliary agent solution. The additive solution was sprayed into the powder within 5 minutes while stirring in a high-speed mixer at 600 rpm. After spraying, heat to 110℃ and stir at 1000 rpm for 15 minutes to initially mix the additives with the powder. The powder after the above treatment was transferred to a reaction vessel, 5L of ethanol / water mixed solution (ethanol to water volume ratio 9:1) was added, the pH was adjusted to 4-5 with acetic acid, and the hydrolysis and condensation reaction was carried out at 60℃ for 2h. After the reaction was completed, the mixture was filtered. The filter cake was washed three times with anhydrous ethanol, with 2L of anhydrous ethanol added each time. The mixture was stirred and washed for 10 minutes before being filtered. The modified silicon-magnesium-aluminum powder was obtained by vacuum drying at 70℃ and -0.08MPa for 6 hours.

[0043] The application of one-step modified magnesium-aluminum silicate powder in polypropylene composites, wherein the polypropylene composites differ from those in Example 1 in that the modified magnesium-aluminum silicate powder is 40 parts. The preparation method of the polypropylene composite material is the same as that in Example 1.

[0044] Comparative Example 2 A method for preparing modified magnesium-aluminum silicon powder, which differs from that in Example 1, is as follows: The pre-anchored powder obtained in step S1 is the modified silicon-magnesium-aluminum powder.

[0045] The application of modified magnesium-aluminum silicate powder in polypropylene composite materials, wherein the polypropylene composite material differs from that in Example 1 in that an equal mass part of modified magnesium-aluminum silicate powder replaces the multifunctional group synergistic modified magnesium-aluminum silicate powder. The preparation method of the polypropylene composite material is the same as that in Example 1.

[0046] Comparative Example 3 An application of natural silica-magnesium-aluminum powder in polypropylene composite material, which differs from that in Example 1, is that in the polypropylene composite material, an equal mass part of natural layered silica-magnesium-aluminum powder replaces the multifunctional synergistic modified silica-magnesium-aluminum powder. The preparation method of the polypropylene composite material is the same as that in Example 1.

[0047] Comparative Example 4 A method for preparing multifunctional group synergistically modified silicon-magnesium-aluminum powder differs from that in Example 1 in that, in step S2, the amount of amino (-NH2) grafting on the surface of the pre-anchored powder is calculated to be 0.28 mmol / g; the amount of macromolecular mixing agent required is calculated based on the measured amount of amino grafting, so that the molar ratio of amino to free carboxyl groups in the macromolecular mixing agent is 1:0.7, then 392 mmol of macromolecular mixing agent is required, and 184.3 g of the macromolecular mixing agent obtained in Preparation Example 1 is used; In step S4, 184.3g of the macromolecular mixed additive calculated in step S2 is used.

[0048] The application of a multifunctional group synergistic modified silica-magnesium-aluminum powder in polypropylene composites is the same as in Example 1; The preparation method of the polypropylene composite material is the same as that in Example 1.

[0049] Comparative Example 5 A method for preparing multifunctional group synergistically modified silicon-magnesium-aluminum powder differs from that in Example 1 in that, in step S2, the amount of amino (-NH2) grafting on the surface of the pre-anchored powder is calculated to be 0.28 mmol / g; the amount of macromolecular mixing agent required is calculated based on the measured amount of amino grafting, so that the molar ratio of amino to free carboxyl groups in the macromolecular mixing agent is 1:1.3, then 728 mmol of macromolecular mixing agent is required, and 342.3 g of the macromolecular mixing agent obtained in Preparation Example 1 is used; In step S4, 342.3g of the macromolecular mixed additive calculated in step S2 is used.

[0050] The application of a multifunctional group synergistic modified silica-magnesium-aluminum powder in polypropylene composites is the same as in Example 1; The preparation method of the polypropylene composite material is the same as that in Example 1.

[0051] Powder characterization tests of multifunctional group synergistic modified silicon-magnesium-aluminum powder: (1) Activation index test: Refer to "T / CSTM 01202-2024 Test method for activation index of organic modified inorganic powder materials"; take 5.00g of modified powder and put it in 100ml of water and stir for 1min. After shaking and standing for 30min, gently pick up the powder floating on the water surface with a filter paper of known mass, and put it together with the filter paper into an oven at 105℃ to dry until constant weight. Weigh the mass of the floating powder. Activation index (%) = (mass of floating powder / total mass of powder sample) × 100%. This is because the surface of unmodified inorganic powder is hydrophilic and will completely settle in water, and the activation index is close to 0. After organic modification, the surface of the powder changes from hydrophilic to hydrophobic and floats on the water surface. The higher the activation index, the better the surface modification effect and the stronger the hydrophobicity.

[0052] (2) Contact angle test: Refer to GB / T 30447-2013 standard "Method for measuring contact angle of nanofilm"; take 2g of modified powder and press it into a disc with a diameter of 13mm and a thickness of 2mm under a pressure of 20MPa. Use Kruss DSA100 optical contact angle meter to test the static contact angle of water droplets on the disc surface using the seat drop method to measure the wettability of solid surface. A contact angle <90° indicates that the surface is hydrophilic (water spreads easily), >90° indicates that the surface is hydrophobic (water forms spheres), and >105° indicates that it is strongly hydrophobic. This is because the surface of unmodified inorganic powder is rich in hydroxyl groups, and the contact angle is usually <10° (superhydrophilic).

[0053] The multifunctional group synergistic modified silicon-magnesium-aluminum powders obtained in each embodiment and comparative example were tested according to the above method, and the test results are shown in Table 1.

[0054] Table 1 Analysis of Test Results: According to the performance test results in Table 1 above, the activation indices of Examples 1-7 are all higher than 96%, significantly higher than the activation indices of 82.4% in Comparative Example 1 and 91.6% in Comparative Example 2. This indicates that the stepwise modification method combining small molecule pre-anchoring with macromolecular grafting efficiently and uniformly coats the surface of the silicon-magnesium-aluminum powder with hydrophobic long-chain alkyl groups, completely transforming it from hydrophilic to strongly hydrophobic. Compared with Example 1, Examples 2 and 3 have a higher pre-anchoring treatment temperature of 120℃ and a higher amount of γ-aminopropyltriethoxysilane of 20g. The activation index of Example 2 is the highest at 98.2%, which indicates that the different conditions form a denser amino anchoring layer, thereby grafting more macromolecular mixed additives. The activation index of Example 3 is slightly lower than that of Example 1, indicating that when the amount of KH550 is too low, the anchoring layer density is insufficient, limiting the subsequent macromolecular grafting amount. The activation index of Example 4 is lower than that of Example 1, indicating that the longer alkyl chains have... It exhibits stronger hydrophobicity and higher surface coverage; while Comparative Example 1, using a one-step modified silicon-magnesium-aluminum powder, shows that due to steric hindrance, only a small amount of macromolecular mixed additives are grafted, resulting in an activation index of 82.4%. This indicates that the macromolecular mixed additives cannot be grafted uniformly and at a high density due to steric hindrance, leaving a large number of exposed hydrophilic areas on the powder surface, thus confirming the defect of the traditional method of "increasing stiffness inevitably reduces toughness"; while Comparative Example 2 uses pre-anchored powder as the modified powder, which demonstrates that the small... Its molecular structure allows it to cover the powder surface well, but its hydrophobic segments are relatively short (propyl), and its hydrophobic effect is not as good as that of macromolecular mixed additives with long-chain alkyl groups. Because it lacks long-chain alkyl groups and carbon-carbon double bonds, its reinforcing effect is limited. In Comparative Example 4, when the amino:carboxyl ratio is 1:0.7, the carboxyl groups are insufficient, the grafting is incomplete, and the activation index is lower than that of Example 1. In Comparative Example 5, when the amino:carboxyl ratio is 1:1.3, although the reaction can be guaranteed to be complete, the excess unreacted additives need to be removed by washing, which increases the process burden and reduces performance.

[0055] Analysis of the contact angle test results shows that the contact angles of Examples 1-7 all exceeded 105°, with Example 2 reaching 114°, indicating a strongly hydrophobic state. This suggests that the modified silica-magnesium-aluminum powder surface is fully covered by long-chain alkyl groups, significantly reducing the interfacial tension with water and greatly improving its compatibility with non-polar resins such as polypropylene. As for the macromolecular mixed additive used in Example 3, its contact angle of 107° is less than that of Example 1 (112°). This demonstrates that the longer the carbon chain, the better the hydrophobic effect, because longer alkyl chains have stronger hydrophobicity and better compact arrangement. The contact angle of Comparative Example 1 was 86°, which is considered moderately hydrophobic, indicating that the one-step grafting of macromolecular mixed additives resulted in uneven coverage, with some areas still exposing the hydrophilic surface. The contact angle of Comparative Example 2 was 95°, which is higher than that of Comparative Example 1, but still lower than that of Examples 1-7. This is because the propyl segment of γ-aminopropyltriethoxysilane is relatively short and has limited hydrophobic ability, failing to achieve the hydrophobic effect of long-chain alkyl groups. The contact angle of Comparative Example 4 was only 101°, which did not reach a strong hydrophobic level, while that of Comparative Example 5 was 108°. This confirms that insufficient carboxyl groups lead to incomplete grafting and insufficient hydrophobic coverage.

[0056] In summary, the multifunctional group synergistic modified silicon-magnesium-aluminum powder prepared in this application successfully grafted macromolecular mixing agents onto the surface of silicon-magnesium-aluminum powder with high density and uniformity via amide bonds by using a stepwise anchoring method combining small molecule pre-anchoring and macromolecular grafting. The higher the activation index, the larger the contact angle and the stronger the hydrophobicity. All embodiments simultaneously satisfy the activation index ≥95% and contact angle >105°, and these two indicators jointly verify the sufficiency and uniformity of surface modification.

[0057] Performance tests of the polypropylene composite materials obtained in each embodiment and comparative example: (1) Tensile property test: including tensile strength (MPa) and elongation at break (%). Referring to GB / T 1040.2-2006 "Determination of tensile properties of plastics - Part 2: Test conditions for molded and extruded plastics", the injection-molded type I dumbbell-shaped specimens (size 160mm×10mm×4mm) were conditioned for at least 24h in a standard environment of temperature (23±2)℃ and relative humidity (50±10)%, and the tensile speed was 50mm / min. The stress-strain curve of the specimen during the tensile process was recorded. Among them, tensile strength (MPa) = maximum tensile force (N) / (specimen width (mm) × specimen thickness (mm)) and elongation at break (%) = (increase in gauge length at break (mm) / original gauge length (50mm)) × 100%; Bending performance test: including bending strength (MPa) and bending modulus (MPa). Referring to GB / T 9341-2008 standard "Determination of bending properties of plastics", the injection-molded specimen (size 80mm×10mm×4mm) was conditioned for at least 24h in a standard environment of temperature (23±2)℃ and relative humidity (50±10)%, with the span set at 64mm. The indenter was used to apply the load downward at a speed of 2mm / min, and the force-displacement curve during the bending process was recorded until the specimen broke or reached the maximum strain. Among them, bending strength (MPa) = (3 maximum bending force (N) × span (mm)) / (2 specimen width (mm) × specimen thickness (mm) squared) and bending modulus (MPa) = (span (mm) cubed × force increment (N) of the initial linear part of the bending force-displacement curve) / (4 specimen width (mm) × specimen thickness (mm) cubed × displacement increment (mm) corresponding to F_f). Notched impact strength test for simply supported beams / cantilever beams: including notched impact strength of simply supported beams (kJ / m) 2 The notched impact strength of the cantilever beam (kJ / m²) was determined by referring to GB / T 1043.1-2008 "Determination of Impact Properties of Plastic Simply Supported Beams Part 1: Non-Instrumental Impact Tests" and GB / T 1843-2008 "Determination of Impact Strength of Plastic Cantilever Beams". Using a Zwick HIT50P simply supported beam impact testing machine, the injection-molded specimens (80mm × 10mm × 4mm) were conditioned for at least 24 hours at a standard environment of (23±2)℃ and (50±10)% relative humidity. The notch type was 2mm deep and 0.25mm at the root of the notch. The pendulum was released with the notch facing away from the impact direction, and the impact energy absorbed and the angle of return of the pendulum after impact were recorded. The impact energy absorbed was read through a dial or electronic sensor. The notched impact strength of the simply supported beam (kJ / m²) was then calculated. 2 = Impact absorbed energy (J) / (sample thickness (mm) × remaining width at notch (mm)), cantilever beam notched impact strength (kJ / m²) 2 = Impact absorbed energy (J) / (sample thickness (mm) × remaining width at notch (mm)).

[0058] (2) Melt Flow Rate (MFR) test: Referring to GB / T 3682.1-2018 "Determination of Melt Mass Flow Rate (MFR) and Melt Volume Flow Rate (MVR) of Thermoplastic Plastics - Part 1: Standard Method", the Zwick Aflow melt indexer was heated to 230℃ and kept at a constant temperature. 5g of PP composite material particles were added to the barrel and compacted to make the material completely melt. Under a load of 2.16kg, the molten material was extruded from a standard die (diameter 2.095mm). A section of extrudate was cut every 30s with a cutting tool. Five sections were cut continuously, and the mass of each section of extrudate was weighed. The average value was taken to reflect the processing fluidity of the material. This is because filling inorganic powder usually reduces the MFR of PP. If the modified powder has good compatibility with PP and is evenly dispersed, the negative impact on fluidity is small, and it may even improve fluidity due to lubrication. The melt flow rate (g / 10min) = 600 average mass of each section of extrudate (g) / cutting time interval (30 seconds).

[0059] (3) Heat distortion temperature (HDT) test: Referring to GB / T 1634.2-2004 "Determination of load distortion temperature of plastics - Part 2: Plastics and hard rubber", the load deflection method was used in the Zwick HDT / Vicat heat distortion temperature tester. The injection-molded sample (size 80mm×10mm×4mm) was conditioned for at least 24h in a standard environment with a temperature of (23±2)℃ and a relative humidity of (50±10)%, and the span was set to 64mm. A bending stress of 0.45MPa was applied and the sample was immersed in a heat-conducting oil (or silicone oil) bath. The initial temperature was room temperature, and the temperature was increased at a rate of 120℃ / h. The temperature at which the deflection of the midpoint of the sample reached the specified value (0.25mm) was recorded as the heat distortion temperature, which is used to reflect the material's ability to resist heat deformation under load. This is because inorganic powder filling can usually improve the HDT of PP, but the powder will restrict the thermal movement of molecular chains. The better the interface bonding between the modified powder and PP, the more significant the HDT improvement.

[0060] (4) Dimensional stability (average shrinkage rate) test: The injection molded sample (100mm×100mm×2mm square plate) was conditioned for at least 24 hours in a standard environment with a temperature of (23±2)℃ and a relative humidity of (50±10)%. The length and width of the square plate were measured with vernier calipers to measure the dimensional stability of the material. This is because inorganic powder filling can reduce the shrinkage rate of PP (the powder itself does not shrink). The better the bonding between the modified powder and the PP interface and the more uniform the dispersion, the lower the shrinkage rate and the higher the dimensional stability. Among them, the shrinkage rate (%) = (mold cavity size (100mm) - actual measured size of the product after placement (mm)) / mold cavity size (100mm) × 100%. The horizontal and vertical shrinkage rates were summed and averaged, and the average shrinkage rate was recorded.

[0061] The polypropylene composite materials obtained in each embodiment and comparative example were tested according to the above method, and the test results are shown in Tables 2 and 3.

[0062] Table 2 The test results for the above mechanical properties (including tensile properties, bending properties, and notched impact strength of simply supported beams / cantilever beams) are presented.

[0063] Analysis of Test Results: Based on the performance test results in Table 2, it can be seen that, firstly, analyzing the tensile performance test results, the tensile strength of Comparative Example 1 is only 33.2 MPa, slightly higher than Comparative Example 3's 31.14 MPa, indicating extremely limited reinforcing effect. Comparative Example 2, at 34.0 MPa, also shows no significant enhancement. This indicates that the macromolecular mixed additive cannot efficiently graft in the one-step method due to steric hindrance, failing to exert its multifunctional reinforcing effect. Example 1, with a tensile strength of 41.2 MPa, is significantly better than Comparative Examples 1 and 2, fully demonstrating the technical advantages of the stepwise anchoring method. Comparative Examples 4 and 5, however, are lower than Example 1. This indicates that in Comparative Example 4, insufficient carboxyl groups prevent some amino groups from reacting with the carboxyl groups to form amide bonds, resulting in incomplete macromolecular grafting. The interfacial bonding is weak; while in Comparative Example 5, although the excess carboxyl group ensures complete reaction, the excess unreacted additive may form a physical adsorption layer, affecting the regularity of the grafted layer and stress transfer efficiency; Example 1 is superior to Example 4, which indicates that C18 long-chain alkyl groups are more fully entangled with the PP molecular chain than C12 long-chain alkyl groups, resulting in better interfacial compatibility and higher stress transfer efficiency; combined with the elongation at break data, comparing the filling amounts of different parts of multifunctional group synergistic modified silica-magnesium-aluminum powder in Examples 1, 2, 6, and 7, from low to high, the overall rigidity of the material is enhanced, the plasticity is reduced, and the elongation at break decreases; while in Example 5, after using copolymer polypropylene instead of homopolymer polypropylene, the elongation at break is much higher than that of the homopolymer PP system, which reflects the high toughness of the copolymer PP itself.

[0064] Then, based on the analysis of the bending performance test results, the bending strength of Example 1 (52.8 MPa) was significantly higher than that of Comparative Examples 1-3, indicating that the modified silicon-magnesium-aluminum powder of the present invention plays an excellent role in rigidity reinforcement in PP. From the influence of the filling amount on the bending strength of Examples 1, 2, 6, and 7, the larger the filling amount, the more significant the increase in bending strength. Combined with the analysis of the bending modulus data, the bending modulus of Example 1 reached 3050 MPa, significantly higher than that of Comparative Example 3 (2173 MPa), indicating that a strong interfacial bond was formed between the modified silicon-magnesium-aluminum powder of the present invention and PP, and the rigid powder effectively bore the bending load. As the filling amount increased from 10 parts to 50 parts, the bending modulus continuously increased from 2350 MPa to 3250 MPa, indicating that the larger the filling amount, the more significant the rigidity reinforcement effect. Example 1 was significantly higher than Comparative Examples 1 and 2, which confirms the significant advantage of the modification method of the present invention in improving the bending modulus. As for Example 7, it reached the highest rigidity level, but its impact performance decreased significantly, so a balance needs to be struck in practical applications.

[0065] Finally, based on the notched impact strength test results of simply supported beams / cantilever beams, the notched impact strength of the simply supported beam in Comparative Example 3 is 24.51 kJ / m. 2 The notched impact strength of the cantilever beam is 4.34 kJ / m. 2 As a reference standard, only the simply supported beam in Comparative Example 1 has a notched impact strength of 23.5 kJ / m. 2 The results were lower than those of Comparative Example 3, confirming the inherent flaw of traditional modification methods that "increase stiffness inevitably reduces toughness." Example 1, however, achieved a breakthrough effect of "increasing both stiffness and toughness." This is attributed to the formation of a flexible transition layer at the interface by the high-density grafted C18 long-chain alkyl groups, which effectively absorbs and disperses impact energy. Example 1 is superior to Example 4, indicating that the longer flexible segments of the C18 long-chain alkyl groups dissipate more energy through segmental movement during impact, resulting in a better toughening effect. Based on Examples 1, 2, 6, and 7, the optimal filler content is 25-40 parts, balancing stiffness and toughness. Comparing Example 1 with Comparative Examples 4 and 5, the influence of the amino to carboxyl ratio verifies that a completely uniform grafted layer achieves the best toughening effect. In contrast, the cantilever beam impact strength of Comparative Example 3 was only 4.34 kJ / m. 2 The impact strength is far lower than that of a simply supported beam (24.51 kJ / m). 2 This is because stress is concentrated at the fixed end during cantilever beam testing, and the agglomeration defects of the unmodified powder are very likely to cause cracks at this point; the impact strength of the cantilever beams in each embodiment after modification is greatly improved, reaching 32.8 kJ / m² in Example 1, which fully proves that high-density grafting eliminates interface defects.

[0066] Table 3 Analysis of Test Results: Based on the performance test results in Table 3, the following analysis shows that, firstly, the MFR test results show that, using the MFR of 1.34 in Comparative Example 3 as a benchmark, the MFR of Comparative Example 1 is 1.28 g / 10 min, indicating poorer flowability. This is because the one-step grafting is uneven, causing powder agglomeration and forming "physical cross-linking points," which increases melt flow resistance. In contrast, the MFR of Example 1 is 1.68 g / 10 min, showing significantly improved flowability. This is because the high-density grafted C18 long-chain alkyl groups act as "molecular lubricants," reducing powder-melt interfacial friction. Combined with the activation index data in Table 1, the MFR is highly positively correlated with the activation index. This is because sufficient modification reduces the interfacial tension between the powder and PP, resulting in more uniform dispersion and lower melt flow resistance. Considering the effect of filler content on MFR in Examples 1, 2, 6, and 7, higher filler content reduces powder spacing and increases flow resistance. This indicates that a filler content of 25-40 parts per unit area maintains good mechanical properties while ensuring acceptable processing flowability.

[0067] Then, based on the HDT test results, the HDT of Example 1 reached 130℃, which is 16℃ higher than that of Comparative Example 3, a very significant improvement. This indicates that the high-density grafted macromolecular functional layer forms a strong interfacial bond, effectively restricting the thermal motion of PP molecular chains at high temperatures and improving the heat resistance of the composite material. The HDT of Comparative Example 1 was only 116℃, only 2℃ higher than that of Comparative Example 3 (unmodified raw powder), with almost no improvement. Comparative Example 2 was 120℃, an improvement of 6℃. Example 1 (130℃) is significantly better than both, which proves that only a complete and high-density multifunctional interfacial layer can effectively constrain the movement of PP molecular chains. Moreover, from Examples 1, 2, 6 and 7, HDT is significantly positively correlated with the filling amount, that is, the higher the powder filling amount, the denser the rigid skeleton and the better the heat resistance. Compared with Example 4, the interfacial layer formed by the C18 chain length in Example 1 is denser and more stable, and has a stronger constraint effect on the molecular chains.

[0068] Finally, analysis of the dimensional stability (average shrinkage rate) test results showed that the average shrinkage rate of Example 1 was only 0.89%, far lower than that of Comparative Example 3 (1.23%). This indicates that the modified magnesium-silicon aluminum powder of the present invention formed a strong interfacial bond with PP, effectively inhibiting PP crystallization shrinkage and significantly improving the dimensional stability of the product. In contrast, the shrinkage rate of Comparative Example 1 (one-step method) was 1.16%, indicating that the one-step modified powder failed to effectively reduce shrinkage. The shrinkage rate of Comparative Example 2 (KH550 only) was 1.08%, indicating some improvement, but the effect was not as good as that of Example 1. Furthermore, the filling amount and shrinkage rate showed a significant negative correlation, that is, the higher the filling amount, the lower the shrinkage rate and the better the dimensional stability. The significant reduction in shrinkage rate is particularly important for components with high dimensional accuracy requirements, such as automotive dashboards and door panels, as it can reduce post-processing steps and improve product yield.

[0069] In summary, this application fills modified magnesium-aluminum silicate powder into polypropylene composites. The magnesium-aluminum silicate powder modified by the stepwise anchoring method significantly improves tensile strength, flexural strength, flexural modulus, and impact performance. It also exhibits excellent processing fluidity, heat resistance, and dimensional stability, achieving a balance between stiffness and toughness and overcoming the pain point of traditional fillers that increase stiffness but inevitably reduce toughness. Furthermore, it further verifies the role of the multifunctional group synergistic modification of magnesium-aluminum silicate powder by combining small molecule anchoring layers with macromolecular functional layers in this application. The small molecule anchoring layer solves the grafting density problem, while the macromolecular functional layer provides compatibility and reactive bonding ability with the PP matrix.

[0070] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A multifunctional synergistic modified silicon-magnesium-aluminum powder, characterized in that, include: A natural layered silicon-magnesium-aluminum powder substrate, and a multifunctional interface modification layer grafted onto the surface of the silicon-magnesium-aluminum powder by chemical bonding; The multifunctional interface modification layer is composed of an amino anchor layer formed by a small molecule aminosilane coupling agent and a macromolecular mixed agent grafted onto the amino anchor layer via amide bonds. The natural layered silica-magnesium-aluminum powder is composed of the following components by mass percentage (100%): ≥28.0% SiO2, ≥32.0% MgO, ≥15.0% Al2O3, ≤3.0% CaO, ≤3.0% Fe2O3, and 10.0-20.0% loss on ignition. The natural layered magnesium-silicon aluminum powder has a particle size D50 of 3-10 μm, a specific surface area of ​​8-15 m² / g, and a Mohs hardness of 2.6-3.

3.

2. The multifunctional group synergistically modified silicon-magnesium-aluminum powder according to claim 1, characterized in that, The small molecule aminosilane coupling agent is γ-aminopropyltriethoxysilane or γ-aminopropyltrimethoxysilane.

3. The multifunctional group synergistically modified silicon-magnesium-aluminum powder according to claim 1, characterized in that, The macromolecular mixed additive is a long-chain alkyl-maleic anhydride monoester-silane and a long-chain alkyl-maleic acid monoester.

4. The multifunctional group synergistically modified silicon-magnesium-aluminum powder according to claim 1, characterized in that, The long-chain alkyl group in the long-chain alkyl-maleic anhydride monoester-silane has 10-18 carbon atoms, and its general structural formula is C0. n H 2n+1 -O-CO-CH=CH-CO-NH-(CH2)3-Si(OC2H5)3.

5. A method for preparing the multifunctional synergistic modified silicon-magnesium-aluminum powder according to any one of claims 1-4, characterized in that, Includes the following steps: S1. Place the dry natural layered magnesium-aluminum silica powder in a high-speed mixer, mix and dilute the small molecule aminosilane coupling agent with anhydrous ethanol at a volume ratio of 1:(2-4), atomize and spray it in, heat it at 100-120℃ for 10-20 min, and obtain the pre-anchored powder. S2. Determine the amount of amino grafting on the surface of the pre-anchored powder obtained in step S1 by acid-base titration or elemental analysis. Calculate the required amount of macromolecular mixed additive based on the number of millimoles of amino groups per gram of powder, so that the molar ratio of amino groups to free carboxyl groups in the macromolecular mixed additive is 1:(0.8-1.2). S3. Disperse the pre-anchored powder obtained in step S1 in an anhydrous organic solvent. The mass-volume ratio of the powder to the anhydrous organic solvent is 1g:3-8ml. Disperse the powder by ultrasonication to form a stable suspension. S4. Dissolve the macromolecular mixed additive calculated in step S2 in an anhydrous organic solvent accounting for 1 / 10-1 / 5 of the total volume to obtain an additive solution. Under nitrogen protection, slowly add the additive solution dropwise to the stable suspension in step S3. The dropwise addition time is controlled at 30-60 min. After the dropwise addition is completed, raise the temperature to 40-60℃ and stir the reaction for 2-6 h to obtain the reaction product. S5. Filter the reaction product from step S4 and wash it 2-3 times with the same anhydrous organic solvent as in step S3. Each time, the mass-to-volume ratio of the filter cake to the solvent is 1g:2-5ml. Stir and wash for 10-15min and then vacuum dry at 60-80℃ for 4-8h to obtain multifunctional synergistic modified silicon-magnesium-aluminum powder with an activation index ≥95% and a contact angle >105°.

6. The method for preparing multifunctional group synergistically modified silicon-magnesium-aluminum powder according to claim 5, characterized in that, In step S1, the amount of the small molecule aminosilane coupling agent is 0.5-2.0% of the mass of the natural layered magnesium silicate aluminum powder.

7. The method for preparing multifunctional group synergistically modified silicon-magnesium-aluminum powder according to claim 5, characterized in that, In step S3, the anhydrous organic solvent is anhydrous tetrahydrofuran, anhydrous dichloromethane, or anhydrous toluene.

8. The method for preparing multifunctional group synergistically modified silicon-magnesium-aluminum powder according to claim 5, characterized in that, In step S5, the vacuum degree of the vacuum drying is ≤-0.08MPa.

9. The application of the multifunctional group synergistic modified silica-magnesium-aluminum powder obtained by the preparation method according to any one of claims 5-8 or the multifunctional group synergistic modified silica-magnesium-aluminum powder according to any one of claims 1-6 in polypropylene composite materials, characterized in that, The polypropylene composite material is composed of the following components by mass: 100 parts polypropylene resin, 10-50 parts multifunctional synergistic modified silica-magnesium-aluminum powder, 0.1-0.5 parts antioxidant, and 0.1-0.5 parts lubricant. Wherein, the polypropylene resin is homopolymer polypropylene or copolymer polypropylene; The antioxidant is one or more of antioxidant 1010, antioxidant 1076, and antioxidant 168; The lubricant is calcium stearate, zinc stearate, or polyethylene wax; The polypropylene composite material is used to manufacture automotive bumpers, dashboards, or door panel structural components.

10. The application of the multifunctional group synergistically modified silica-magnesium-aluminum powder according to claim 9 in polypropylene composite materials, characterized in that, The preparation method of the polypropylene composite material includes the following steps: Polypropylene resin, multifunctional synergistic modified magnesium-aluminum silicate powder, antioxidant, and lubricant are added to a high-speed mixer and mixed at 500-800 rpm for 3-5 minutes. Then, the mixture is fed into a twin-screw extruder for multi-segment melt blending. The extruder temperatures are set as follows: Zone 1 160-180℃, Zone 2 180-200℃, Zone 3 / 4 190-210℃, Zone 5 180-200℃, and the die head temperature 180-200℃; the screw speed is 250-350 rpm, and the feed speed is 15-25 rpm. The material is extruded, cooled, and granulated to obtain polypropylene composite material particles; Polypropylene composite material particles are injection molded on an injection molding machine at an injection temperature of 190-210℃ and a mold temperature of 30-50℃.